In vitro cytotoxic and genotoxic analysis of Garcinia humilis crude extract (Bioscience Journal, 2022)
Garcinia humilis, known commonly as achachairú or bacupari, has great medicinal value. Their fruits have pharmacological, antibacterial, antioxidant, and anticancer properties. Therefore, the objective of the present study was to evaluate the cytotoxicity and genotoxicity of G. humilis crude extract in breast tumor cells. Cytotoxicity was determined using the Resazurin reduction assay and genotoxicity by the single cell gel electrophoresis assay (Comet assay) on human MCF-7 cells. Crude extract of G. humilis was cytotoxic only when used at high concentrations (IC50 = 5.084 mg mL-1). The Comet assay showed that the crude extract did not induce genotoxicity at 1 and 5 mg mL-1 but did show signs of DNA fragmentation and DNA fragmentation at 10 mg mL-1. The cytotoxic activity against breast adenocarcinoma cells at high concentrations suggests that this medicinal plant could be used with caution and must be further studied to understand better its therapeutic and toxicological potential in the human body.